Effect and mechanism of inhibiting ZNF139 on apoptosis in human gastric cancer cell line BGC823 - Liqiao Fan; Bibo Tan; Yong Li; Qun Zhao; Yü Liu; Dong Wang; Zhidong Zhang (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: To investigate the role of ZNF139 played in GC cell apoptosis and to explore its mechanism. Methods: Expression of ZNF139 in GC tissues, adjacent normal tissues, GC cell lines MKN28, SGC7901, BGC823 and in gastric epithelial cell line GES-1 were tested. Then ZNF139-specific siRNA was transfected into BGC823 cells. Viability, cell cycle and apoptosis of GC cells were detected. Survivin, x-IAP, caspase-3, Fas, p53, Bcl-2 and Bax genes were detected. Results: The results showed that ZNF139 was highly expressed in gastric cancer tissues and cells. FCM indicated that after transfection, GC cells in G0/G1 phase was significantly increased, and those cells was significantly reduced in G2/M phases after transfection, apoptosis rate of BGC823 cells was increased significantly. After ZNF139- siRNA was transfected into BGC823, QPCR and Western blot showed that expressions of Survivin, x-IAP and Bcl- 2 were significantly down-regulated, while expressions of caspase-3 and Bax were significantly up-regulated. Conclusion: ZNF139 functions to promote apoptosis resistance of BGC823.